2014
DOI: 10.1007/s12562-014-0744-8
|View full text |Cite
|
Sign up to set email alerts
|

Progress on larval and juvenile nutrition to improve the quality and health of seawater fish: a review

Abstract: In seedling production of seawater fish, providing appropriate nutrition is a necessity for successful production of quality larvae and juveniles. Mass-produced live prey organisms, such as the rotifer Brachionus plicatilis species complex and brine shrimp Artemia spp., alone do not provide sufficient nutrition to the larvae and juveniles of seawater animals. This inadequacy has led to various problems related to fish quality and health, including increased incidence of morphological and behavioral abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Another relevant aspect is the composition of prey, specifically the HUFA and DHA contents. Similar to what has been widely demonstrated in fish larvae, the importance of DHA in the physiology of paralarvae may be related with visual and neuronal development as have been suggested by numerous studies (Navarro & Villanueva , ; Tocher and Takeuchi ). Newly hatched O. vulgaris display a high DHA content ranging between 17–27% of total FA (Navarro & Villanueva ; Okumura et al .…”
Section: Resultssupporting
confidence: 70%
“…Another relevant aspect is the composition of prey, specifically the HUFA and DHA contents. Similar to what has been widely demonstrated in fish larvae, the importance of DHA in the physiology of paralarvae may be related with visual and neuronal development as have been suggested by numerous studies (Navarro & Villanueva , ; Tocher and Takeuchi ). Newly hatched O. vulgaris display a high DHA content ranging between 17–27% of total FA (Navarro & Villanueva ; Okumura et al .…”
Section: Resultssupporting
confidence: 70%
“…To date, all studies on finfish have shown that they require the usual essential amino acids (EAA) (NRC, 2011;Oliva-Teles, 2012;Takeuchi, 2014). The development of commercial aquatic feeds has traditionally been based on FM as the primary protein source, due to its high protein content and well balanced EAA profile (Nguyen et al, 2009;NRC, 2011;Oliva-Teles, 2012) with high levels of digestible EAA such as lysine (Lys), methionine (Met) and leucine (Hall, 1992).…”
Section: Proteins/amino Acidsmentioning
confidence: 99%
“…For instance, enrichment with Spirulina increased amino acid levels in artemia (Bhavan, Devi, Shanti, Radhakrishnan, & Poongodi, 2010) important amino acids such as taurine could be transferred to larvae. Taurine is known as a free organic acid that plays important role in lipid digestion, absorption and osmoregulation (Kim, Matsunari, Takeuchi, Yokoyama, Murata, & Ishihara, 2007;Takeuchi, 2014). The taurine concentration of rotifer and artemia are lower than that of copepods (Van der Meeren, Olsen, Hamre, & Fyhn, 2008).…”
Section: Introductionmentioning
confidence: 99%